The economic structure of a construction enterprise - Shpakov , A.; Yakymchuk , T.; Bodianskyi , O.; Siedinkin , O. (Ways to Improve Construction Efficiency, 2024)
The economic structure of a construction enterprise is the foundation of its stability and competitiveness. Construction companies engaged in the production of material goods require an effective organization of their economic structure for optimal resource allocation, management functions, and cost control at all stages of the project. Construction is a complex and multifaceted process that includes technological, financial, and human resource aspects. Effective management of the economic structure determines the success of the company and allows it to adapt to changing market conditions. The main components of the economic structure include financial, production, personnel, and organizational elements. The organization of internal processes impacts the economic efficiency and adaptability of the enterprise. The role of financial management, cost planning, and resource utilization control is crucial for achieving the company's stability and sustainability. It is also important to highlight the significance of innovative management approaches, especially the implementation of cutting-edge information technologies that contribute to improving efficiency and reducing costs. The analysis of the economic structure allows for the assessment of factors such as material, equipment, labor costs, as well as the costs of management functions. An important component is also the use of modern software solutions and systems for automating management processes, which reduces transaction costs and improves project execution control. The use of ERP systems and other technologies ensures effective management and increases transparency at all stages of construction. This not only improves the company’s financial performance but also enhances its ability to adapt to changing external conditions. Additionally, it is important to consider the role of the personnel component in the economic structure of the enterprise. Well-trained staff are the driving force behind the implementation of new management approaches and technologies.